PENGARUH UMUR PEMOTONGAN TERHADAP KADAR PROTEIN KASAR DAN SERAT KASAR Indigofera zollingeriana - Hutabarat, Jestika; Erwanto, Erwanto; Wijaya, Agung Kusuma (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
The aims of research to know the effect of cutting age on crude protein and crude fiber of Indigofera zollingeriana. The study was done based on Completely Randomized Design (CRD) with 3 treatments and 4 replications. The treatments in this study were : 1) U40 (40 days of cutting age), 2) U50 (50 days of cutting age), and 3) U60 (60 days of cutting age). Indigofera zollingeriana being cuts at 1 m height from the ground surface and plots of land measuring 3 x 3 m2. The results showed that the effect of cutting age significantly (P < 0.01) affect crude protein and crude fiber of Indigofera zollingeriana. Crude protein content of Indigofera zollingeriana with cutting age of 40, 50, and 60 days were 24,76%, 26,00% and 27,03% respectively and crude fiber content of Indigofera zollingeriana with cutting age of 40, 50, and 60 days were 20,72%, 23,08%, and 25,41% respectively. Key word : Indigofera zollingeriana, cutting age, crude protein and crude fiber.